BUILDING GENDER EQUALITY FROM AN EARLY AGE: IMPLEMENTATION OF PHYSICAL PLAY IN EARLY CHILDHOOD EDUCATION - Rita Nofianti; Nurhalimah Tambunan; Anggun Febri Purwanti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This research aims to analyze the implementation of physical play as a medium for gender-responsive learning in early childhood education. Gender stereotypes formed from an early age can limit children's developmental potential. Through a descriptive qualitative approach, this study explores how physical play can be an effective means to build gender equality awareness in children aged 4-6 years. Research findings show that physical play designed with a gender-responsive approach can reduce gender stereotypes, increase children's self-confidence regardless of gender, and develop motor skills inclusively. The implications of this research provide practical recommendations for early childhood educators in designing learning activities that support gender equality from an early age.